An integrated model for productivity prediction of cyclic steam stimulation with horizontal well. Issue 3 (9th April 2019) - He, Congge; Xu, Anzhu; Fan, Zifei; Zhao, Lun; Shan, Fachao; Bo, Bing
Abstract: As the accurate productivity prediction of cyclic steam stimulation with horizontal well (CSSHW) is essential for its effective utilization in heavy oil reservoirs, a novel integrated model for predicting productivity of CSSHW was proposed in this paper. Firstly, governing equations to predict thermophysical parameters of injected steam in the horizontal well were established. On the basis, the heating model for radius of hot fluid zone and steam zone were derived respectively according to a more realistic temperature distribution of formation. Then, coupled with heating model, the productivity prediction model was established according to the principle of equivalent percolation resistance. Then, comparisons have been made among the new model results, CMG STARS results, and measured data to verify its accuracy. Finally, after the new proposed model is validated, the effects of steam quality and injection rate on heating radius and oil production were analyzed in detail. The results indicate that the result of new model is in good agreement with that of CMG STARS and measured data, verifying the correctness of the model. In addition, the radius of hot fluid zone and steam zone both decreases with horizontal well length because of the heat losses as the steam flows along the horizontal wellbore. Influential factor analysis shows that high steam quality and steam injection rate can improve heating radius and cumulative oil production. Abstract : The equations for radius of hot fluid zone and steam zone were derived respectively according to a more realistic temperature distribution of formation. On the basis, the productivity prediction model was established according to the principle of equivalent percolation resistance.